Thermal Injuries in Veterinary Forensic Pathology. (September 2016) - Wohlsein, P.; Peters, M.; Schulze, C.; Baumgärtner, W.
Localized thermal injuries in animals may be caused by exposure to fire and radiant heat, contact with hot items including hot liquids or steam, inhalation of hot air, and exposure to cold temperatures. In addition, animal fire victims may have intoxications caused by smoke gas. This article reviews the causes, pathogenetic aspects, morphological findings, additional investigations, differential diagnoses, and causes of death in various forms of thermal injuries. Since these cases do not occur frequently in diagnostic pathology, they represent a challenging task in general but also with respect to forensic or criminal aspects, such as whether a lesion represents an accidental or nonaccidental effect. Besides detailed information about the circumstances at the location, thermal injuries in animals require a thorough morphological evaluation, including additional investigations in conjunction with a profound knowledge about the possible lesion spectrum and suitable additional investigations.